Solar cycle effect delays onset of ozone recovery - Dameris, Martin; Matthes, Sigrun; Deckert, Rudolf; Grewe, Volker; Ponater, Michael (Geophysical Research Letters, 2006)
Short- and long-term changes of total ozone are investigated by means of an ensemble simulation with the coupled chemistry-climate model E39/C for the period 1960 to 2020. Past total ozone changes are well simulated on both, long (decadal) and short (monthly) timescales. Even the 2002 Antarctic ozone anomaly appears in the ensemble. The model results indicate that the 11-year solar cycle will delay the onset of a sustained ozone recovery. The lowest global mean total ozone values occur between 2005 and 2010, although stratospheric chlorine loading is assumed to decline after 2000. E39/C results exhibit a significant increase of total ozone after the beginning of the next decade, following the upcoming solar minimum. The observed ozone increase in the second half of the 1990s is reproduced by E39/C and is identified as a combined post- Pinatubo and solar cycle effect rather than the beginning of a sustainable ozone recovery.